Labour, Management and the Public - Goldenberg, H. Carl (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1964)
SummaryIn this paper, presented at the Fifth National Labour, Management Seminar, University of British Columbia, October 1963, the author expresses the fruits of his long experience as a mediator and an arbitrator in labour-management disputes. The parties must face the facts; the law cannot settle everything; a continuous bargaining system would prove valuable.